Hand Washing Awareness: A Community Health Initiative - Aboud, Diane; Bustard, Catherine; Lagodski, Gail; MacDonald, Wilma (Operating Room Nurses Association of Canada Journal, 1999)
In planning for O.R. Nurses Day in November 1998, the Ottawa Regional Operating Room Nurses Association ( O.R.O.R.N.A.), felt a need to make a special contribution to their community. In doing so they had an idea to establish a Back to Basics Health Awareness Campaign. Members believed this to be a very important community health initiative. While many ideas were considered, the need for handwashing hygiene awareness was determined to be a priority. By promoting handwashing, O.R.O.R.N.A. wanted to increase positive health awareness both professionally and in the general community. As operating room nurses we daily prescribe to many clinical procedures that prevent the spread of bacteria and infectious diseases. It seems, however, that as a society with a busier than ever lifestyle, many of the basic principles of hygiene are not being followed.